Intermediation and matching in insurance markets - Uwe Focht; Andreas Richter; Jörg Schiller (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2009)
This paper addresses the role of independent insurance intermediaries in markets where matching is important. A controversial matter in the discussion concerning insurance intermediation is the issue of compensation customs and how the latter affect prices, rents and advice quality in insurance markets. This work compares a fee-based with a commission-based system. We show that in a situation with a non-strategic intermediary both remuneration systems are payoff-equivalent. In a second step, allowing for strategic behavior, we discuss the impact of remuneration on the quality of advice. The analysis shows that the possibility of mismatching can provide the intermediary with substantial market power which however does not translate into mismatching as long as consumers have rational expectations. We offer a rationale for the use of contingent commissions. In addition, this paper addresses whether or not the recent ban of any commission payments as introduced in countries such as Denmark and Finland is an appropriate market intervention.
urn:nbn:de:bsz:100-opus-3650
Keywords: G22; G24; L51; 360; Versicherungsvermittlung; Versicherungsmarkt; Matching; Versicherungsökonomik; Vergütungssystem; Regulierung; Theorie; Dänemark; Finnland